PELUANG MEMILIKI RUMAH SENDIRI DI KOTA BANDA ACEH - Marliesna, Abubakar Hamzah, Samsul Rizal. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2014)
Abstract: As we know that the development of infrastructure, especially housing problems is really needed by everyone and had so much built by developers both inside the city and outside the city. This residential development ranging from the type, design and technical specifications are varied, it is intended to be accessible by consumers. Although developers already provide some conveniences such as the ability to repay in accordance with the selected type, there are still plenty of civil servant (PNS) as well as those working in the private sector has not been able to buy/own their own home on the grounds of various considerations interests respectively. Then the objectives to be achieved in this study were: to analyze the characteristics of the household that is income, level of education, status/position in the main job, age, gender, number of household members and marital status that affect the probability of having their own house in Banda Aceh city and estimating the magnitude of the probability of significant explanatory variables affect the probability of having their own house in Banda Aceh city. Explanatory variables used in this model consists of a variable income, number of household members, gender, education level, employment sector, age and marital status will affect the probability of households to own their own home. The data used is secondary data from the National Socio-Economic Survey 2011, which contains the results of a survey conducted by BPS. The respondent xample is 418 household. This thesis focuses on the area of Banda Aceh as well as using the logit model estimation. The result of calculations show that the proportion of households in the city of Banda Aceh who own their own home around 53.83%, with the proportion who are not self owned approximately 46.17%. The analysis showed that the variables household size and age significantly affect the chances of having their own home with a significance level of 5%. The coefficient of logistic regression was equal to 0.14004 meaning that if family members increase one more hence the probability of the ownership of the house will increase by 0.45 (45%). Keywords: Logit Model, Home Ownership, Banda Aceh. Abstrak: Seperti diketahui bahwa pembangunan sarana fisik khususnya masalah perumahan sangat diperlukan oleh semua orang dan sudah begitu banyak dibangun oleh pengembang baik di dalam kota maupun diluar kota. Pembangunan perumahan ini mulai dari type, design dan spesifikasi teknis yang bervariasi, hal ini dimaksudkan untuk dapat dijangkau oleh para konsumen. Meskipun pengembang sudah memberikan beberapa kemudahan seperti dapat mengangsur sesuai dengan kemampuan type yang dipilih, ternyata masih banyak baik Pegawai Negeri Sipil (PNS) maupun yang bekerja disektor swasta belum mampu membeli/memiliki rumah sendiri dengan alasan berbagai pertimbangan kepentingan masing-masing. Maka tujuan yang ingin dicapai dalam penelitian ini adalah untuk menganalisis karakteristik rumah tangga yaitu pendapatan, tingkat pendidikan, jenis pekerjaan, usia, jenis kelamin, jumlah anggota rumah tangga dan status perkawinan yang mempengaruhi peluang memiliki rumah sendiri di Kota Banda Aceh dan mengestimasi besarnya probabilitas variabel penjelas yang signifikan mempengaruhi peluang memiliki rumah sendiri di Kota Banda Aceh. Variabel-variabel penjelas yang digunakan dalam model ini terdiri dari variabel pendapatan, jumlah anggota rumah tangga, jenis kelamin, tingkat pendidikan, sektor pekerjaan, usia dan status perkawinan yang akan mempengaruhi probabilitas rumah tangga untuk memiliki rumah sendiri. Data yang digunakan adalah data sekunder hasil Survey Sosial Ekonomi Nasional 2011 yang berisi hasil survey yang dilakukan oleh BPS. Sampel responden yang dianalisis sebanyak 418 rumah tangga. Tesis ini memfokuskan pada daerah kota Banda Aceh serta menggunakan estimasi dengan model logit. Hasil penelitian menunjukkan bahwa proporsi rumah tangga di Kota Banda Aceh yang memiliki rumah sendiri sekitar 53,83%, dengan proporsi yang bukan rumah milik sendiri sekitar 46,17%. Hasil analisis menunjukkan bahwa variabel jumlah anggota rumah tangga dan usia berpengaruh nyata terhadap peluang memiliki rumah sendiri dengan tingkat signifikansi 5%. Koefisien regresi logistik pada variabel Jumlah Anggota Rumah Tangga sebesar 0,14004 berarti apabila jumlah anggota rumah tangga bertambah 1 orang maka probabilitas kepemilikan rumah sendiri akan meningkat sebesar 0,45 (45%). Kata Kunci : Model Logit, Kepemilikan Rumah, Banda Aceh.